Skill-Biased Technical Change in U.S. Manufacturing: A General Index Approach - Badi H. Baltagi; Daniel P. Rich (Institute for the Study of Labor (IZA), 2003)
This article applies recent advances in productivity and efficiency measurement to the evaluation of skillbiased technical change. Using the general index approach we are able to establish an explicit and unconstrained time path for nonneutral technical change between production and nonproduction labor in U.S. manufacturing industries over the 1959-1996 period. Our findings confirm the prevailing interpretation in the labor economics literature that substantial reductions in the relative share of production labor are attributable to a sustained period of nonneutral technical change. However, we find that skill-biased technical change effects are most evident prior to 1983. This predates the diffusion of personal computer technologies in the workplace and the dramatic wage structure changes associated with the 1980?s. In contrast to prevailing alternatives, the general index approach also permits us to explain observed shifts in relative labor demand as a combination of price-induced substitution, nonhomothetic output effects and skill-biased technical change responses to a range of proposed elements.
Keywords: O33; C33; J23; 330; skill biased technical change; nonneutral technical change; labor demand; manufacturing; panel data; skill; wage inequality; Qualifikation; Technischer Fortschritt; Arbeitsnachfrage; Lohnstruktur; Verarbeitendes Gewerbe; Schätzung; Vereinigte Staaten